EFFICIENCY OF USE OF FREQUENCY CONVERTER WITH SMOOTH CONTROL OF ASYNCHRONOUS MOTOR SPEED - Qurbonov Nurali Abdullayevich; Qurbonova Munisaxon Sanjar qizi; Tog’ayev Axror Ikrom o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the efficiency of a frequency converter when using it for smooth control of the rotational speed of electric drives with an asynchronous motor (AD). The ratios of voltage and frequency of the supply network for various loads are given.